THE EFFECTIVENESS OF USING YOUTUBE AS MEDIA IN TEACHING SPEAKING AT MAN 4 KEDIRI - Mariyana, Yunita (Jurnal Pendidikan Bahasa Inggris Proficiency, 2019)
Using YouTube as media is one of the ways to teach speaking. Using YouTube as media help students to be better independent English speaker and makes the students easier in learning English. The main purpose of the study is to examine the effectiveness of using YouTube as media on students’ speaking score of the eleventh grade IIS-2. Quantitative was selected as a research approach, whereas the research design used was Quasi Experimental by using posttest-only design. This research used two classes which became experimental and control group. The experimental group was taught speaking using YouTube as media, while the control group was taught using picture as media. To collect the data, post speaking tests in experimental and control group were administered. Data were analyzed by using t-test. The findings indicated that score of the experimental group higher than the control group. Thus, it can be concluded that using YouTube as media in teaching speaking is effective.